Exports, agglomeration and workforce diversity: An empirical assessment for German establishments - Stephan Brunow; Luise Grünwald (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Theoretical and empirical contributions on export behavior highlight the importance of firms' productivity and their levels of economies of scale on firms' export success in `foreign markets. In the context of agglomeration economies, firms enjoy produc-tivity gains when they are located close to competitors or upstreaming industries and they benefit from knowledge spillovers and other positive externalities. In such a stimulating environment, firms become more prone to be exporters. Beyond the role played by externalities, firms may benefit when they employ a diverse workforce and when the interaction of distinct knowledge and related problem-solving abilities increases productivity and secures export success. In this paper, we ask whether German firms (i.e., establishments) benefit from localization and urbanization exter-nalities and face higher export proportions. We also control for a variety of estab-lishment characteristics and workforce diversity. For this purpose, a comprehensive German data set that combines survey data and administrative data is used. While controlling for firm heterogeneity in a fractional response model, we provide evi-dence that manufacturing establishments and smaller establishments (up to 250 employees) benefit most from externalities and especially from knowledge spillover. There is weak evidence supporting the benefit of workforce diversity; however, that factor could explain between-establishment variation.
Keywords: D22; F14; M14; 330